Travel-Time Plots for Refraction Stations near Kodiak, Alaska. - Shor, George G., Jr (1972)
These travel-time plots and station notes are intended to serve as an appendix to the paper 'Marine Seismic Refraction Studies near Kodiak, Alaska'. A discussion of the results will be found in that paper and in a paper being prepared by von Huene on the structure of the Kodiak area. These station notes, of less general interest, are intended for those who wish to look at the plots on which the interpretations are made, and reinterpret for themselves if they desire. The original records are on file at the Marine Physical Laboratory of the Scripps Institution of Oceanography, La Jolla, California. All of the travel-time plots given are 'reduced plots' in which the travel-time has had subtracted from it the quantity(distance/7.0 km per sec). All stations except LF 19-20 were worked with water-delay time removed, and without topographic corrections to reduce the sea floor to a flat datum. Since the topography was quite smooth in most cases (as shown by the topographic plot at the bottom of each travel-time plot), topographic corrections to datum should not make any significant difference. The horizontal scale (distance in seconds) on each plot is the travel time of the direct water wave; the multiplier to convert it to kilometers is given as the water velocity in each case.